Comparative analysis of term usage in the text books for schools ``In the World of Elementary Mathematics'' - Kaklauskienė, Danutė (Lietuvos matematikos rinkinys, 2004)
The article deals with the scope of lexical units textbooks and exercise books on mathematics for elementary schools, frequencies of title words are compared. Mathematical terms occurring in the texts are selected, their frequencies regarding separate school grades have been investigated.
Keywords: text; term; sample; descriptive statistics; percentage analysis